A guide to condition scoring of zebu cattle - Nicholson, M.J.; Butterworth, M.H. (International Livestock Centre for Africa, 1986)
Discusses the need for condition scoring and how to condition score. Presents a description of condition scores and shows how to use the data. Illustrates with diagram the distinctive anatomical parts of importance in condition scoring and presents photographs of cattle in good condition and emaciated ones.